Design and implementation of MIMO-long term evolution-advanced to support larger bandwidth - Alashqer, Aws Zuheer Yonis (2013)
The migration of mobile communication technologies are divided into four generations. Long Term Evolution (LTE) is called LTE rel-8, the evolution of LTE led to new technology referred to as LTE-Advanced, is the true fourth generation (4G) evolution step, with the first release of LTE (rel-8) which was labeled as “3.9G”. LTE-Advanced is a mobile broadband access technology founded as a response to the need for the improvement to support the increasing demand for high data rates. The standard for LTE-A is a milestone in the development of Third Generation Partnership Project (3GPP) technologies. Carrier Aggregation is one of the most distinct features of LTEAdvanced that makes the bandwidth extension of up to 100 MHz thus the theoretical peak data rate of LTE-A may be even up to 1 Gbps. This proposed system presents new LTE-Advanced depending on carrier aggregation to obtain better performance of the system. The new design of LTE-Advanced offers higher peak data rates than even the initial LTE-A; while the spectrum efficiency has been amended; As a result, the aggregated LTE-A will support 120 MHz instead of 100 MHz in order to obtain higher peak data rate access up to 4 Gbps. The system was applied with 8x8 Multiple Input Multiple Output (MIMO) using different modulation techniques: QPSK, 16 QAM, and 64 QAM. From the simulation results, it is clear that proposed LTE-Advanced with 64 QAM has high values of throughput in case of depending code rate equals to 5/6 with 8x8 MIMO.